2020
DOI: 10.1016/j.exer.2020.108047
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of miR-200 clusters promotes epithelial to mesenchymal transition in human conjunctival epithelial cells

Abstract: Epithelial to mesenchymal transition (EMT) contributes to fibrosis associated pathologies including scarring of different ocular tissues. Recently targeting EMT is seen as an appropriate therapeutic approach for different fibrosis related eye diseases such as macular degeneration or glaucoma surgery related fibrosis. Nevertheless, for ocular surface diseases, target genes specific for particular cell type or condition are still undefined. This study aimed to expose the complex regulatory mechanisms that trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Targeting EMT is seen as a novel therapeutic approach for fibrosis-related eye diseases such as the degeneration of the macula or glaucoma-surgery-related fibrosis [51]. The methylation of DNA bases plays an important role in the epigenetic regulation of gene expression, including the modulation of miR-141 expression in normal and cancer cells [52].…”
Section: Mir-141-an Important Molecular Regulator Of Emt In Cancer An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting EMT is seen as a novel therapeutic approach for fibrosis-related eye diseases such as the degeneration of the macula or glaucoma-surgery-related fibrosis [51]. The methylation of DNA bases plays an important role in the epigenetic regulation of gene expression, including the modulation of miR-141 expression in normal and cancer cells [52].…”
Section: Mir-141-an Important Molecular Regulator Of Emt In Cancer An...mentioning
confidence: 99%
“…Since it is known that miR-141 is involved in EMT, the aberrant methylation of CpG islands near the start of transcription of miR-141/200c cluster is associated with their inappropriate silencing in neoplastic cells and phenotypic conversion in normal cells [52]. The DNA demethylating agent, 5-Azacytidine (5-AzaC), inhibits the transition of human conjunctival epithelial cells towards a mesenchymal phenotype and induces the expression of the miR-200 cluster, including miR-141, suggesting the potential for the invention of epigenetics-based strategies for the treatment of diseases associated with EMT [51].…”
Section: Mir-141-an Important Molecular Regulator Of Emt In Cancer An...mentioning
confidence: 99%
“…The RT-PCR-based array directed at members of miR-200 family as the key regulators of EMT process in human conjunctival epithelial cells. It further indicated that DNA demethylation of promoters of miR-200 loci is very important for reverting the EMT in human conjunctival epithelial cells, suggesting the prospective for the developing new epigenetic-based therapeutic methods for treating conjunctival conditions associated with EMT [ 37 ].…”
Section: Role Of Mirnas In the Conjunctival Disordersmentioning
confidence: 99%
“…Among the fibrotic processes that could account for cGVHD-related dry eye disease, EMT is a possible candidate for the process because the ocular surface epithelium loses the capability to secrete mucins when the epithelial cells undergo the transition to a mesenchymal phenotype [ 23 ]. Several studies have shown that EMT contributes to various fibrotic diseases of the kidneys, lungs, and liver and the ocular surface epithelium [ 97 , 98 , 99 ] and retinal pigment epithelium [ 100 ] in the eye. For example, 40% of fibroblasts in kidney fibrosis arise from epithelial cells via local EMT triggered by inflammatory stress, and 15% of fibroblasts are derived from the bone marrow under inflammatory stress [ 101 ].…”
Section: Immune-mediated Fibrosismentioning
confidence: 99%